MULTICULTURALISM OF COMMUNICATIVE PROCESSES IN THE GLOBALIZED WORLD - Дротянко, Л. Г.; Жолдоков, В. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the authors are trying to reveal the peculiarities of communicative processes in the countries, where the phenomenon of multiculturalism considerably influences on the intercultural relations of representatives of different ethnical groups in the globalization conditions.